Primary Intracranial Tumors - Barros Da Silva Junior, Erasmo; Buzetti Milano, Jerônimo (IntechOpen, 2019)
This book covers specific chapters with fundamental and current concepts about the main primary intracranial tumors, aimed at general neurosurgeons, neurologists, oncologists, radiotherapists, and residents. They are everyday situations from the subspecialist routine that can become challenging for professionals outside referenced centers or working alone.